Erythema gyratum perstans. - Bonafé, J.L.; Duhault, P.; Dupin, P. (European Journal of Pediatric Dermatology, 2018)
The Authors report 3 new cases of Colcott Fox erythema gyratum perstans, occurring sporadically in a small girl and in two adolescent girls respectively, its clinical course being indefinite. Its is characterized by annular lesions with a slightly squamous fringe on the inner edge. Pruritus is variable. On pathological examination, orthoparakeratotic hyperkeratosis, exoserosis, and a slight dermal inflammatory infiltrate can be shown. Direct immunofluorescence with anti-immunoglobulins is negative. The other laboratory examinations rule out the diagnosis of annular dermatosis, and of other annular erythemas, particularly Darier's centrifugal annular erythema. The Authors review the previously reported relevant cases. The etiology of the disorder is unknown. It may involve an inflammatory and/or immunologic mechanism, with consumption and resynthesis of an inflammatory mediator at any site of the skin surface.